Detection of industrially potential enzymes of moderately halophilic bacteria on salted goat skins - BİRBİR, MERAL; ÇAĞLAYAN, PINAR (WALTER DE GRUYTER GMBH, 2018)
Aim: This study aimed to isolate moderately halophilic bacteria from salted goat skins, to characterize these microorganisms and to determine their industrially important enzymes such as amylase, catalase, oxidase, caseinase, cellulase, DNase, lipase, lecithinase, protease, pullulanase, urease, phospholipase, xylanase and beta-galactosidase. Methods: Enzymes of these bacteria, isolated from skin samples belonging to eight countries and identified using phenotypic and genotypic methods, were examined in agar media. Results: Thirty-nine isolates were fairly similar to species of genera Staphylococcus, Bacillus, Salinicoccus, Gracilibacillus, Chromohalobacter and Halomonas. Various carbon sources were utilized, and all isolates produced enzyme. Enzyme-producing species were Staphylococcus saprophyticus subsp. saprophyticus, Staphylococcus arlettae, Bacillus pumilus, Gracilibacillus dipsosauri, Salinicoccus roseus, Bacillus licheniformis, Chromohalobacter beijerinckii, Staphylococcus xylosus, Halomonas eurihalina, Staphylococcus equorum subsp. equorum, Halomonas zhanjiangensis, Halomonas venusta and Chromohalobacter canadensis. Fairly high percentage of isolates produced protease (87%) and catalase (100%). While more than 50% of isolates produced lipase (64%), beta-galactosidase (59%) and oxidase (56%), less than 50% of isolates produced urease (46%), caseinase (28%), amylase (26%), lecithinase (8%) and cellulase (5%). Conclusion: We detected that moderately halophilic bacteria on skins produced important enzymes, which may be used in diverse industrial applications in leather, feed, detergent, paper, food, chemical, medical, pharmaceutical, textile industries.
Keywords: Moderately halophilic bacteria; Industrially important enzymes; Biochemical characteristics; Leather industry; Molecular identification; SP-NOV.; STAPHYLOCOCCUS-SAPROPHYTICUS; CHROMOHALOBACTER; SEQUENCE; DATABASE; ARCHAEA